Asymmetries and opportunities: Power and inequality in Fairtrade wine global production networks. Issue 2 (13th July 2018) - Herman, Agatha
Abstract : Fairtrade is changing. The hegemonic certified system, governed by Fairtrade International, has seen some high‐profile withdrawals by major processors and retailers in recent months, which is leading to both proponents and critics questioning who, and what, the system is for. While the certified system has seen increasing conventionalisation, there remains at its core a mission to make trade fair, empower those marginalised in global trade and foster sustainable livelihoods. Taking a global production network (GPN) framework supports a critical exploration of the market, social and political asymmetries of this international system of production and distribution. Drawing on empirical evidence from the wine industry, this paper uses a production‐space perspective to critically reflect on some of the key relations within Fairtrade GPNs. While there are many positive impacts, particularly in social development, producers have experienced a conventionalisation of supply chains, a lack of contextual responsiveness and limited engagement with the global system. These indicate a continuation of power asymmetries that are intersecting, multiscalar and evolving. Although these are from wine industry case studies, anecdotal evidence suggests that they are not uncommon experiences and even a hint of unfair, disempowering and unsustainable trading practices negatively impacts both these producers' livelihoods and the reputation of the Fairtrade system as a whole. Nonetheless, there remains significant producer buy‐in indicating that the ideals of Fairtrade retain currency. This therefore presents a critical opportunity for Fairtrade to actively address the market, social and political inequalities that persist in its GPNs and re‐establish itself as a leader in the ethical marketplace.